SPECTRUM OF HELICOBACTER PYLORI IN HUNDRED PATIENTS PRESENTING WITH PERFORATED DUODENAL ULCER - Haider, Iqbal; Hussain, Dildar; Muhammmad, Ali (Journal of Postgraduate Medical Institute, 2011)
Objective : To find out the frequency of Helicobacter pylori in patients presenting with perforated duodenal Methodology : This observational study was conducted at Lady Reading Hospital Peshawar from July 2004 to January 2005 on 100 patients with confirmed diagnosis of perforated duodenal ulcer fulfilling the inclusion criteria. A semi-structured Questionnaire was designed for the study. Results : Out of a total of 200 patients operated for perforated duodenal ulcer 100 patients were fulfilling study criteria. Among these100 patients 80 were males and 20 were females. The participants were ranging from 18 to 72 years in age with mean age of 47.02±13.42 years. Helicobacter pylori were found in 80(80%) patients on histopathology and 65 (65%) patients on rapid urease test Infection rates were maximum in the elderly and those belonging to poor socioeconomic class. All infected patients were treated with triple regimen eradication therapy comprising of clarithromycin, Proton Pump Inhibitor (PPI), and amoxicillin for 14 days. The patients were not followed to confirm eradication status. Conclusion : The spectrum of H. Pylori infection is very high in patients with duodenal ulcer perforation. An early and appropriate H. Pylori eradication therapy may prevent duodenal ulcer perforation. ulcer.